The Effect of Personal Selling "Yakult Lady" and Brand Image on Consumer Loyalty - marlina, Lili; Jamaluddin, Jamaluddin; Hastuti, Puji; Elliyana, Ela (Business and Entrepreneurial Review, 2023)
The purpose of this study was to determine the effect of personal selling and brand image on consumer loyalty for yakult drinks in Indonesia. The research was conducted in Indonesia, the research period was July - September 2023. The research population is consumers of drinks with the yakult brand in Indonesia, of which the exact number cannot be known. This study used Non-probability Purposive Sampling technique and for a sample of 100 respondents, but less than 100 complete questionnaires were considered usable. The results showed that personal selling and brand image have an effect on consumer loyalty, including through repat orders and consumer satisfaction with the yakult lady as personal selling